Metabolites profiling and fingerprinting of the ethanolic extract of Zingiber zerumbet (L.) Roscoe ex Sm. - Nur Zahratun Najah Mohd Razali (Tanjong Malim, 2022)
Metabolites profiling and fingerprinting of the ethanolic extract of Zingiber zerumbet (L.) Roscoe ex Sm. by Nur Zahratun Najah Mohd Razali